Moving north: different factors influencing male and female mexican migration to United States - Canudas-Romo, Vladimir (Papeles de Población; Vol. 10 Núm. 39 (2004): Papeles de Población, 2021)
This paper employs survival analysis to study the Mexican patterns of migration to the United States for working purposes. The model focuses on certain factors which have been distinguished previously as characteristics of labour migration: age, family responsibility, family network, education, labour status and calendar year. Special emphasis has been put on distinguishing between male and female characteristics. The data used derives from the EDER, a retrospective survey elaborated in Mexico. Estimates show a reduction in the migration risk for men and women due to employment in Mexico and the formation of a union, respectively. The most important contribution of this project is the emphasis on the change over time of the influence of these different factors on the risk to migrate to the United States.